The Characteristics and Experiences of Summer Visitors to Goat Island Marine Reserve, New Zealand - Race, Sharon (Auckland University of Technology, 2011)
Goat Island Marine Reserve (GIMR) is New Zealand’s oldest marine protected area, located on Auckland’s northern east coast. Established in 1975, GIMR has been well researched by marine biologists, but the social aspects have received little attention. This study is the first published empirical research on the characteristics and experiences of its visitors. A self-reply questionnaire-based study was undertaken between 12 December 2010 and 13 January 2011, using the real-time-satisfaction (RTS) measurement. The study (n=305) investigated peak summer visitors’ demographics, characteristics, satisfaction levels and knowledge of marine protection. Results reveal a diversity of visitors who primarily identify with GIMR as a place to ‘swim with the fish’. Visitors are mostly satisfied but their marine protected area (MPA) knowledge is limited. A distinct change to the tourism life-cycle of the area has taken place; once a casual scuba diving location in a rural setting, urbanisation is enveloping the region and tourism is developing. Visitor numbers have increased more than 3000% since 1975 and the site’s social carrying capacity exceeds management-planned levels. In this study, visitors were dissatisfied with a number of aspects, primarily the number of people on the beach, parking and the lack of in-water management of people and boats. Recent fatalities and near-drownings at GIMR have also highlighted the latter aspect. The study identified several key issues, including a lack of on-site staff, inaccurate advertising, the site’s four names, language barriers and a lack of on-site interpretation, which represent the bigger picture of uncontrolled tourism growth in a highly protected natural area. Results indicate there is support for strong managerial approaches to limit visitor numbers and restrict certain activities, such as commercial tourism. The study also profiles the GIMR visitor and develops a new Marine Reserve Visitor Experience model. Marine ecotourism is emerging as an important market in the marine tourism and wildlife tourism sectors. Marine reserves are, however, highly protected areas of the ocean, which are vulnerable to human visitation and require focussed social-management interventions. Understanding the characteristics and experiences of New Zealand’s most popular marine reserve will help inform management decisions so that GIMR can be preserved for future generations.
Keywords: Marine tourism; Goat Island Marine Reserve; New Zealand; Post-positivism ontology; Real-time-satisfaction (RTS) measurement; Marine Reserve Visitor Experience (MRVE) model